2017
DOI: 10.1186/s12966-017-0464-4
|View full text |Cite
|
Sign up to set email alerts
|

Stirring the motivational soup: within-person latent profiles of motivation in exercise

Abstract: BackgroundThe purpose of the present study was to use a person-oriented analytical approach to identify latent motivational profiles, based on the different behavioural regulations for exercise, and to examine differences in satisfaction of basic psychological needs (competence, autonomy and relatedness) and exercise behaviour across these motivational profiles.MethodsTwo samples, consisting of 1084 and 511 adults respectively, completed exercise-related measures of behavioural regulation and psychological nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
37
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 48 publications
9
37
3
1
Order By: Relevance
“…Taylor and Stebbings (), for example, argue that need fulfillment should have an impact on well‐being on both levels, assigning similar importance to both levels. However, echoing argumentation in previous work (Lindwall et al, ; Neubauer, Schilling, & Wahl, ), we argue that the within‐person perspective is more essential since SDT makes predictions concerning within‐person processes, and investigating within‐person processes requires taking a within‐person perspective with regard to both study design and data analysis (Hamaker, ).…”
supporting
confidence: 70%
“…Taylor and Stebbings (), for example, argue that need fulfillment should have an impact on well‐being on both levels, assigning similar importance to both levels. However, echoing argumentation in previous work (Lindwall et al, ; Neubauer, Schilling, & Wahl, ), we argue that the within‐person perspective is more essential since SDT makes predictions concerning within‐person processes, and investigating within‐person processes requires taking a within‐person perspective with regard to both study design and data analysis (Hamaker, ).…”
supporting
confidence: 70%
“…Furthermore, previous studies omitting integrated regulation have shown profiles high in identified and intrinsic motivation (i.e. similar to our moderate-autonomous cluster) to be associated with higher exercise participation (Castonguay & Miquelon, 2017;Friederichs et al, 2015;Lindwall et al, 2017), which is contradictory to our results (i.e. moderateautonomous cluster is strictly speaking the cluster with the least amount (21.9%) of patients who became active).…”
Section: Relationship Between Motivational Profiles and Exercise Chancontrasting
confidence: 99%
“…Given OIT's central, though rigid, distinction between autonomous and controlled motivation, it was expected that both cluster types would be found in the present study. In line with previous research (Friederichs et al, 2015;Lindwall et al, 2017;Miquelon et al, 2016), a high autonomous cluster paired with low controlled motivation scores was clearly identified. However, there was less support for a purely controlled cluster showing high controlled but low autonomous regulations.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…We have therefore used the following labeling concerning the three different profiles: most empowering profile, less empowering profile, and least empowering profile. While prior research has used wording such as high, moderate, and low (e.g., , we considered it more appropriate to differentiate between the different profiles by using adverbs (see Lindwall et al, 2017). The main reason for this was due to rather high self-report values of autonomy-supportive, task-involving, and socially supportive behaviors in the least empowering profile.…”
Section: Latent Profile Analysismentioning
confidence: 99%